APASITAS PEMERINTAH INDONESIA DALAM MENGHADAPI BENCANA KONTEMPORER PADA PANDEMI COVID-19 UNTUK MENDUKUNG KEAMANAN NASIONAL - hal ichbhal; adi subiyanto; ernalem bangun; pujo widodo; wilopo wilopo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The capacity of the Government of Indonesia is urgently needed in dealing with contemporary disasters, especially during the Covid-19 pandemic. The impact of disasters will disrupt community resilience where if the government in its capacity as a policy maker, especially when large-scale natural disasters occur, is not immediately resolved, it will greatly affect national security. This study uses a qualitative method with a descriptive exploratory approach. Data collection by observation, in-depth interviews and documentation. Data analysis technique with qualitative data analysis techniques Miles and Huberman. The research results found that it is important to formulate and oversee disaster management and mitigation programs in the RPJMN every 5 years (2020-2024). The Indonesian government must establish cooperation with Japan, which has already implemented various effective policies in disaster risk management. The conclusion from this study is that capacity building efforts that should be carried out by the Government of Indonesia to anticipate and cope with contemporary disasters are the need to use technology in disaster management, disaster education for the community, and realizing community regeneration/resilience. Increasing government capacity during the Covid-19 pandemic can be carried out by following the direct example of Japan's success in disaster management so that national security is maintained.